TERCEIRIZAÇÃO NA PRESTAÇÃO DE SERVIÇOS PÚBLICOS: ANÁLISE DO PERCURSO DA USP (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
This paper presents the perspectives of outsourcing in Brazil, used as a means of workforce flexibility and as a driver of competitiveness in business activity, but also as a management tool for services in public administration; as well as its impacts on Brazilian public service and its transformation. It traces the path of the possibility of outsourcing both core and support activities in companies and investigates the repercussions and parallels within the University of São Paulo, through new economic and administrative paradigms of public administration, particularly with the development of managerialism, using as objects of analysis the budget, human resource management, the expanses by area of the university, and the internal regulatory resolutions.